2020
DOI: 10.1101/2020.04.27.065227
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrative transcriptomic analysis of SLE reveals IFN-driven cross-talk between immune cells

Abstract: The systemic lupus erythematosus (SLE) is an incurable autoimmune disease disproportionately affecting women and may lead to damage in multiple different organs. The marked heterogeneity in its clinical manifestations is a major obstacle in finding targeted treatments and involvement of multiple immune cell types further increases this complexity. Thus, identifying molecular subtypes that best correlate with disease heterogeneity and severity as well as deducing molecular cross-talk among major immune cell typ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
(65 reference statements)
1
3
0
Order By: Relevance
“…BAFF has been shown to be commonly overexpressed in SLE, which plays a vital role in the proliferation and differentiation of B cells and is strongly involved in the pathogenesis of SLE (34). A recent study revealed that TNFSF13B expression was elevated in SLE and highly positively correlated with monocytes (31), which was consistent with our results of CIBERSORT and scRNA analyses. Belimumab, the only effective biological therapy that targets BAFF, has been authorized for clinical use in SLE (35).…”
Section: B C D E F Asupporting
confidence: 90%
See 1 more Smart Citation
“…BAFF has been shown to be commonly overexpressed in SLE, which plays a vital role in the proliferation and differentiation of B cells and is strongly involved in the pathogenesis of SLE (34). A recent study revealed that TNFSF13B expression was elevated in SLE and highly positively correlated with monocytes (31), which was consistent with our results of CIBERSORT and scRNA analyses. Belimumab, the only effective biological therapy that targets BAFF, has been authorized for clinical use in SLE (35).…”
Section: B C D E F Asupporting
confidence: 90%
“…In addition, clinical data indicated that the main obstacle to target treatment of SLE patients is its heterogeneity in the involvement of different cell types. The clinical heterogeneity of SLE and its related involvement of different cell types has made it challenging to design accurate therapy (31). Therefore, finding the major cell types involved in the pathogenesis of SLE and MetS comorbidity and exploring a cell-specific molecular program is of vital importance.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression analysis was performed using DESeq2-3.5 in RNA Flow, via Wald hypothesis testing and parametric fit typing and using the Benjamin-Hochberg method for multiple testing correction (see Robinson et al, 2019). IFN signature gene lists were obtained from published reports (IFN-GSEA (Panwar et al, 2020), IFN-Vital (El-Sherbiny et al, 2018). Publicly available differential gene expression datasets from atherosclerotic plaque macrophages were also obtained (Chai et al, 2018; Fernandez et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…A transcriptomic study conducted in SLE patients showed that gene signatures associated with interferon signaling is significantly dysregulated ( 38 ), although current efforts targeting IFN in SLE have not been successful. A more recent study in this field profiled six major immune types in SLE patients by single-cell RNAseq and found a unique set of genes in monocytes, including two well-known immune modulators for SLE and RA therapeutics ( TNFSF13B/BAFF : belimumab and IL1RN : anakinra, respectively) ( 39 ). A single cell transcriptomic study in Crohn’s patients revealed a gene program associated with inflamed tissue, consisting of genes expressed by plasma cells, inflammatory mononuclear phagocytes, and activated T cells ( 40 ).…”
Section: Maintenance Of Immunologic Tolerance In Humans and Its Role In Autoimmunitymentioning
confidence: 99%